2021
DOI: 10.1111/ppc.12954
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate communication levels of nursing students: Predictive role of empathic skills and nursing communication course

Abstract: Purpose This study aims to determine the compassionate communication levels of nursing students and the predictive roles of empathic skills and nursing communication courses. Design and Methods This descriptive study was conducted with 430 nursing students and data were analyzed using a descriptive information form, Compassionate Communication Scale (CCS), and Empathic Skill Scale (ESS). Findings A positive relationship was found between the students’ ESS and CCS scores (r = .23 p = 0.001). Empathic skills (β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The topic of touch as an essential part of nursing practice was also identified in a descriptive survey study of 430 nursing students (57.9% of which were female) in which student nurse empathy skill scores were positively correlated to the nursing students’ compassionate communication scores. 31 Nursing student empathy scores predicted compassionate conversations and use of expressive touch. These findings indicated that nursing student empathy, an essential part of nursing practice, and nurses’ use of expressive touch as a form of compassionate communication also may be positively correlated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic of touch as an essential part of nursing practice was also identified in a descriptive survey study of 430 nursing students (57.9% of which were female) in which student nurse empathy skill scores were positively correlated to the nursing students’ compassionate communication scores. 31 Nursing student empathy scores predicted compassionate conversations and use of expressive touch. These findings indicated that nursing student empathy, an essential part of nursing practice, and nurses’ use of expressive touch as a form of compassionate communication also may be positively correlated.…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicated that nursing student empathy, an essential part of nursing practice, and nurses’ use of expressive touch as a form of compassionate communication also may be positively correlated. 31 …”
Section: Resultsmentioning
confidence: 99%
“…In total, 63 articles were included for full-text review. From these, 44 unqualified articles were eliminated, such as unable to obtain full text, duplicate content or incomplete data, inconsistent research object and content, and Öztürk and Kaçan, 2022, Turkey [11] Total Kaplan and Tülüce, 2021, Turkey [12] Total Oh, 2019, South Korea [13] Total: n = 247…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
“…Xu et al, 2020, China [25] Total Zheng et al, 2020, China [26] Total: n = 472 Ge et al, 2020, China [27] Total: n = 300 Lu and Chen, 2018, China [28] Total Yang et al, 2019, China [29] Total non-cross-sectional research type. Finally, 19 studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] met the inclusion criteria as shown in Figure 2.…”
Section: Stratification Facilitates Cluster Samplingmentioning
confidence: 99%
See 1 more Smart Citation